2015
DOI: 10.1007/s00784-015-1399-2
|View full text |Cite
|
Sign up to set email alerts
|

Two-year clinical performance of a two-step etch-and-rinse adhesive in non-carious cervical lesions

Abstract: The clinical effectiveness of the XP Bond was excellent after 2 years of clinical service. Long-term clinical evaluations are necessary to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…In a good accordance with other studies, the TBS values varied within their respective groups. These variable values have previously been described as being due to structural inhomogeneities within the samples, e.g., dentinal sclerosis and inter-individual dentin consistencies [25,26]. Overall, the obtained results are within a comparable range when related to other research.…”
supporting
confidence: 79%
“…In a good accordance with other studies, the TBS values varied within their respective groups. These variable values have previously been described as being due to structural inhomogeneities within the samples, e.g., dentinal sclerosis and inter-individual dentin consistencies [25,26]. Overall, the obtained results are within a comparable range when related to other research.…”
supporting
confidence: 79%
“…As the dentin bonding agent, a two-step etch-and-rinse adhesive Prime&Bond XP was used in this study due to its well-established clinical performance [56][57][58]. Moreover, the in vitro study showed an increase in its reliability (µTBS) by nearly 110% after one year of aging [59].…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion largely determines the success or failure of composite resin (CR) restorations. Although various adhesive systems have been developed for reliable CR restorations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), each product has unique characteristics that must be considered in clinical practice. Compared to dentin, adhesion to enamel was achieved at an early stage by etching the enamel surface with phosphoric acid (PA) (15).…”
Section: Introductionmentioning
confidence: 99%